2014
DOI: 10.1007/s12026-014-8598-9
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune thyroid disease and rheumatoid arthritis: relationship and the role of genetics

Abstract: Autoimmune thyroid disease (AITD), known as the most common organ-specific autoimmune disorder, is frequently accompanied by other organ and non-organ-specific autoimmune diseases, including rheumatoid arthritis (RA). Although the exact pathogenic mechanisms of the coexistence of autoimmune disorders are still not completely defined, genetics, immune defects, hormones and environmental factors may play key roles in polyautoimmunity. In this review, the prevalence of AITD and antithyroid autoantibodies in RA pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 62 publications
0
39
0
Order By: Relevance
“…The close relationship of ATD with rheumatologic disease has led to speculation on possible reasons for the association [30,31]. There are considerable similarities in genetics and a significant overlap in clinical presentation between several CTD and ATD even in the absence of welldefined CTD [16,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The close relationship of ATD with rheumatologic disease has led to speculation on possible reasons for the association [30,31]. There are considerable similarities in genetics and a significant overlap in clinical presentation between several CTD and ATD even in the absence of welldefined CTD [16,31].…”
Section: Discussionmentioning
confidence: 99%
“…There are considerable similarities in genetics and a significant overlap in clinical presentation between several CTD and ATD even in the absence of welldefined CTD [16,31]. There may therefore at least in some ATD patients be a generalized autoimmune process with systemic clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that genetic factors have pleiotropic effects and predispose to a number of different diseases , but the fetal adaption as a consequence of maternal RA might also induce epigenetic changes that increase the accumulation of diseases, e.g., RA, in the offspring .Thus, our study cannot determine the underlying biologic mechanisms, i.e., the role or contribution of genetic factors and factors related to the intrauterine environment. Genetic factors might explain the excess morbidity when it comes to RA in the offspring, and genetic factors showing pleiotropic effects might also explain the occurrence of other diseases such as autoimmune thyroid disease . However, the results might also partly be due to factors related to an impact of maternal RA itself on the fetal environment, e.g., an impact due to disease activity or medical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, autoimmune diseases are a growing and disturbing health problem, especially as the autoimmune process is activated by genetic and environmental factors that are difficult to identify, and leads to the development of concomitant diseases in other systems. In AITDs, intolerance is caused by the interference with T-cells function and the production of antibodies against the specific cell antigens (Iddah et al, 2013;Pyzik et al, 2015). The autoimmune reaction is possible because of the polymorphisms in major histocompatibility genes (human leukocyte antigen (HLA)), thyroid-specific genes, immunoregulatory genes, and may be sparked by various exogenous (environmental) factors i.e.…”
Section: The Immunopathology Of Autoimmune Thyroid Diseasesmentioning
confidence: 99%